Predictive Factors for Outcome of First Allogeneic Transplant for Elderly Patients With Acute Lymphoblastic Leukemia - Bazarbachi, Abdul Hamid; Labopin, Myriam; Kroger, Nicolaus; Brecht, Arne; Blaise, Didier; Clausen, Johannes; Fanin, Renato; Einsele, Herman; Cavanna, Luigi; Itala-Remes, Maija; Bulabois, Claude Eric; Kundgen, Lukas; et al. (Clinical Lymphoma, Myeloma and Leukemia, 2021)
Introduction/Background: The treatment of acute lymphoblastic leukemia (ALL) in patients older than 70 is extremely challenging with dismal outcome. Allogeneic stem cell transplantation (alloHCT) has seen many advancements in the last decades showing benefits in younger ALL patients, but this treatment modality is decreasingly used with increasing age due to high treatment-related mortality. Patients and Methods: We identified 84 ALL patients 70 to 84 years old allografted In 2002 to 2019 from a matched related (23%), unrelated (58%), haploidentical (17%), or cord blood (2%) donor at EBMT participating centers with a median follow-up of 23 months. Results: The 2-year relapse incidence (RI) and non-relapse mortality were 37% and 28%, respectively, and 2-year leukemia-free survival (LFS), overall survival (OS) and GVHD-free, relapse-free survival (GRFS) were 35%, 39% and 23%, respectively. The strongest predictor of outcome was disease status at transplant whereby patients in first complete remission (CR1) had >50% 2-year OS, reflected in multivariate analysis (MVA) with significant improvement in RI, LFS, and GRFS (HR 0.23, 0.49, and 0.54, respectively). Furthermore, karnofsky score ≥90 reflective of good functional status positively influenced non-relapse mortality in both univariate and MVA (HR 0.37), and interestingly, donor CMV positivity appeared to negatively affect RI, LFS and OS in univariate analysis and RI in MVA (HR 2.87). Conclusion: Our data suggest that alloHCT is an option for elderly ALL patients, particularly those carefully selected and transplanted in CR1 especially if failed or without access to novel non-chemotherapy-based approaches.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic stem cell transplantation; CMV positivity; Complete remission; Graft-versus-host disease; Haploidentical transplantation; Treatment-related mortality